EFFORTS TO IMPROVE CRITICAL THINKING SKILLS AND INTEREST IN LEARNING MATHEMATICS USING THE INTEGRATED NUMBER HEAD-TOGETHER PROBLEM-BASED LEARNING MODEL - Fathin, Aizza Zakkiyatul; Gunawan, Gunawan; Untarti, Reni; Kusuma, Jaka Wijaya; Sugiastuti, Sugiastuti (International Journal of Economy, Education and Entrepreneurship (IJE3), 2023)
This study aims to improve students' critical thinking skills and interest in learning mathematics through the application of Problem-Based Learnin (PBL)-Numbered Head Together (NHT) learning. This research is a Classroom Action Research (PTK) which is carried out for two cycles. The subjects of this study were 26 grade VIII D students at SMP Negeri 1 Gumelar for the 2022/2023 school year. Data collection was carried out with three instruments, namely observation sheets, tests, and non-tests. The results showed that students' critical thinking skills and interest in learning mathematics increased. In the initial condition, students' critical thinking skills before learning were not completed then after learning in the 2nd cycle classical completeness was achieved with a percentage of 85.4% of students who were completed. Increased critical thinking skills are also in line with increased interest in learning mathematics. Students' interest in learning mathematics before learning had an average score of 51.19 with the medium category and in the 2nd cycle obtained a score of 63.31 with a high category in accordance with the research target. This is supported by the increase in the percentage of PBL-NHT learning implementation from cycle 1 by 83% to 92% in cycle 2 for both teacher and student activities